Chronic equine hepacivirus infection in an adult gelding with severe hepatopathy. Issue 3 (3rd July 2019) - Tegtmeyer, Birthe; Echelmeyer, Julia; Pfankuche, Vanessa M.; Puff, Christina; Todt, Daniel; Fischer, Nicole; Durham, Andy; Feige, Karsten; Baumgärtner, Wolfgang; Steinmann, Eike; Cavalleri, Jessika‐M. V.
Abstract: Background: Equine hepacivirus (EqHV) in equids represents the closest homologue to hepatitis C virus (HCV) infecting humans. A majority of HCV infected patients develop a chronic course of infection leading to liver fibrosis, cirrhosis and liver failure. However, in horses mostly transient mild subclinical infections are reported for EqHV to date. Objectives: EqHV can be involved in chronic liver diseases of horses. Methods: Biochemical parameters in serum samples were measured. Viral load was determined using qPCR. Next generation sequencing (NGS) of serum was performed. Liver tissue was stained with haematoxylin and eosin and analysed for viral RNA with fluorescent in situ ‐hybridization. Results: The horse showed symptoms of severe hepatopathy and was chronically infected with EqHV. Viral RNA was detectable in the liver during disease. To rule out other infectious agents NGS was performed and showed the highest abundance for EqHV. The identified virus sequence was similar to other circulating equine hepaciviruses. Conclusions: EqHV can be associated with liver disease in horses. Whether it causes the disease or contributes in a multifactorial manner needs further investigation. Abstract : Equine hepacivirus (EqHV) is the closest homologue of hepatitis C virus (HCV) to date and was recently identified to infect equine liver cells, however, the clinical relevance remains elusive. Here, we describe a case of a horse with severe hepatopathy and chronic EqHV infection.